Trimetazidine effects on intracellular Са2+ ion concentration in HL-60 human promyelocytes - E. I. Astashkin; M. G. Glezer; S. V. Grachev (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To investigate the effects of an anti-ischemic medication trimetazidine on Са2+ ion metabolism in human leukocyte and monocyte precursors – HL-60 promyelocytes.Material and methods. HL-60 cells were cultivated in vitro. Changes in intracellular free Са2+ ion concentration were registered with fluorescent Са2+ probes Fura-2. Results. For the first time it was demonstrated for differentiated and non-differentiated HL-60 cells that an antianginal agent trimetazidine suppressed the activity of plasmatic membrane store operated Са2+ channels (SOC channels). Importantly, trimetazidine did not cause Са2+ ion release from the stores and did not open SOC channels, in contrast to other SOC channel inhibitors, e.g., miconazole. In open SOC channels, trimetazidine and miconazole targeted the same binding areas.Conclusion. The results obtained demonstrate additional trimetazidine effects, linked to selective SOC channel blockade. It provides new potential explanations for trimetazidine effects on electro-inert cells (e.g. blood phagocytes) and its effects in myocardial ischemia.